The Impact of Content Marketing Development - Eva Mirza Syafitri; Muhammad Supriyanto; Ina Syarifah; Windi Setyo Ningrum (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of content marketing in companies focuses on the production and distribution of relevant content. This development aims to attract social media users to follow the activities of PT Berniaga Sinergi Nusantara Madiun, fostering a more positive relationship between the company and potential customers while expanding the company’s reach and influence on the Instagram platform. The purpose of this study is to identify the content and writing style used on the Instagram account of PT Berniaga Sinergi Nusantara Madiun. This analysis aims to understand the aspects that need improvement to make the produced content more effective in capturing the attention of potential customers.The method employed in this research is Research and Development (R&D), which involves stages such as data collection, planning, product development, design validation, product revision, and product testing. The process is expected to result in Instagram content that is relevant and consistent, designed to attract the attention of the targeted customers. The findings indicate that after the content marketing development, Instagram insights showed an increase, with 53.9% of the audience being followers and 46.1% being non-followers. These results demonstrate that the development of content marketing has a significant impact on PT Berniaga Sinergi Nusantara Madiun